Analisis Kurikulum Merdeka Belajar Materi PAI pada Kelas 10 SMK Negeri 1 Depok Yogyakarta - Amalia, Jihanna; Achadi, Muh. Wasith (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The purpose of this study is to analyze the Merdeka Curriculum Learning (Kurikulum Merdeka Belajar) in the subject of PAI (Islamic Religious Education) and moral character applied at SMK Negeri 1 Depok Yogyakarta. The main goal of the Merdeka Curriculum is to prepare students for spiritual maturity, wisdom, and noble character. This research uses qualitative library research method and involves the analysis of content description. Data is collected through observation, in-depth interview, and documentation study. The results of the analysis indicate that the Merdeka learning achievement formulation contains comprehensive competencies and scope of materials in the form of narratives that are adjusted to the developmental stage of students in phase E for grade 10. The ideal learning objective formulation consists of two components: First, attitude, knowledge, and skills competencies; Second, the content, which is core knowledge. The learning objective flow formulation describes the coverage and stages of learning from the beginning to the end of the phase in a linear manner.